A model of pre-pubertal broiler breeder estradiol-17β levels predicts advanced sexual maturation for birds with high body weight or short juvenile day-length exposure. (19th April 2019) - van der Klein, S A S; Hadinia, S H; Robinson, F E; Bédécarrats, G Y; Zuidhof, M J
ABSTRACT: As broiler breeders face increased reproductive challenges specifically related to overfeeding, a clear understanding of the physiological effects of BW and rearing photoperiod on reproductive development is needed. The objective was to use mathematical models to compare plasma estradiol-17β (E2 ) concentration to characterize the effect of BW and rearing photoperiod on E2 levels. A 2 × 3 factorial arrangement of treatments was used. Hens (n = 180) were fed with a precision feeding system to allocate feed individually to achieve the breeder-recommended BW curve (Standard) or to a BW curve reaching the 21 wk target at 18 wk (High). Hens were on 8L:16D, 10L:14D, or 12L:12D photoschedules during rearing and were photostimulated at 21 wk. Age at first egg (AFE) was recorded. Plasma E2 levels were determined weekly between week 20 and 28. Two modified Gompertz models described E2 level as a function of (a) chronological or (b) physiological (relative to AFE) age. Timing of E2-inflection point was compared between models and treatments. Differences were reported as significant at P ≤ 0.05. The chronological age model inferred that High BW reduced the duration between the E2-inflection point and AFE, whereas the physiological age model inferred that High BW only reduced the duration between photostimulation and the E2-inflection point. Hens on the Standard BW treatment had a longer period between photostimulation and the E2-inflection point compared to hens on the High-BW treatment (11.03 vs. 1.50 wk, respectively, based on physiological age). Hens on the 12L:12D photoschedule had a longer period between photostimulation and the E2-inflection point compared to hens on the 8L:16D or 10L:14D photoschedule, both in the Standard and High BW (28.91 vs. 1.78 and 2.40 wk, 2.65 vs. 0.93 and 0.94 wk, respectively, based on physiological age). The described methodology and results provide quantitative insight into E2 dynamics and serves as a model for future endocrinological studies in poultry reproduction.